Correlation of biologically effective dose and the tumor control in Stage I (<5 cm) non-small cell lung cancer with stereotactic ablative radiotherapy: a single institutional cohort study. (29th November 2017) - Jeon, Wan; Ahn, Sung-Ja; Kim, Young-Chul; Oh, In-Jae; Park, Chul-Kyu; Jeong, Jae-Uk; Yoon, Mee Sun; Song, Ju-Young; Nam, Taek-Keun; Chung, Woong-Ki
Abstract : The excellent regional control was conferred with a prescription of more than BED10 of 100 Gy in Stage 1 non-small cell lung cancer with stereotactic ablative radiotherapy. Abstract: Backgrounds: Stereotactic ablative radiotherapy (SABR) is one of the newly developed innovative radiotherapy and of which optimal dose prescription needs to be standardized. We aimed to investigate the dose–response relationship for patients with SABR. Methods: Fifty-three patients with Stage I non-small cell lung cancer patients, who underwent SABR between November 2006 and January 2015, were evaluated retrospectively. Thirteen patients (24.5%), who refused the surgery were included and 40 patients (75.5%) were medically inoperable at diagnosis. The median age was 74 years. The median SABR dose was 50 Gy in 3–8 fractions and the median biologically effective dose (BED;α/β = 10) was 105.6 Gy (range: 60–160.53 Gy). Results: The median follow-up was 37.1 months. The 1 and 3 year local control rates were 91.7% and 85.1%. The 3 year overall and progression-free survival rate were 63.3% and 47.5%, respectively, and freedom from progression was 62.2%. Local control rate and 3-year overall survival according to tumor size was 100% and 79.4% in T1 tumors in a while 61.8% and 45% in T2a tumors. The 3-year local and regional control by BED10 was 79.4% and 69.4% in ≤100 Gy vs. 89.1% and 100% in >100 Gy ( P = 0.526, 0.004). Dyspnea more than Grade 3 was reported in six (11.3%) patients and Grade 1 chest pain was shown in five (9.4%) patients. Conclusions: The excellent regional control was conferred with a prescription of more than BED10 of 100 Gy, which also might be needed to achieve better local tumor control in T2a patients with tolerable lung function.